(untitled) (Świat Idei i Polityki, 2007)
The author is interested in the issue of responsibility for quoting other people's statements in materials spread on the Internet. The author analyses the circumstances connected with the use of private statements on the websites of public communicators and on so-called private websites. The author pays attention to the change in the range of the idea of authorisation in relation to publication on the Internet. At the same time, she indicates the fact of obliteration of changes between the status of a communicator and a recipient of information. The commonness and easiness of publishing and the possibility of making use of various codes and forms of presentation on the Internet make it difficult to specify the group of entities responsible for spreading other people's statements. However, application of these criteria makes it possible to specify the range and to mark out the limits of legal responsibility borne by them.